Associations of dietary linoleic acid and alpha linolenic acid intake with cardiovascular, cancer and all-cause mortalities in patients with diabetes: NHANES 1999-2008 - Jiang, Mianmian; Zhu, Huiping; Zhou, Xiaoding; Zhai, Xiaobing; Li, Shiyang; Ma, Wenzhi; Liu, Keyang; Eshak, Ehab S. (Frontiers in Clinical Diabetes and Healthcare, 2024)
ObjectiveTo investigate the association between the dietary intake of linoleic acid (LA) and alpha linolenic acid (ALA) with mortality outcomes in patients with diabetes.Participants3,112 U.S. adults aged≥20 years.SettingBasic information was collected at baseline of the National Health and Nutrition Examination Survey (NHANES). Serum CRP (mg/dL), total protein (g/L), waist circumference (cm), fasting blood glucose (mmol/L), white blood cell count, serum LDL-C, and serum HDL-C were also measured. Daily diets were also recorded using a 24-hour dietary review to produce the individuals’ intake of LA and ALA. The association between tertiles of LA and ALA intake with mortality was analyzed by weighted Cox models adjusted for the main confounders.Main outcome measuresThe study included 3,112 adults with diabetes from the National Health and Nutrition Examination Survey (NHANES) from 1999 to 2008. Death outcomes were ascertained by linkage to the database records through 31 December 2015.ResultsSubjects with a high intake of LA (T3) had 17% [hazard ratio (HR) 0.83, 95% CI 0.70 to 0.99) and 48% (HR=0.52, 0.35 to 0.80)] reductions in all-cause mortality and cardiovascular mortality, respectively, compared with subjects with lowest intake (T1). Similar results were observed for ALA, HR of cardiovascular mortality was 0.55 (0.38 to 0.81) and for all-cause mortality was 0.85 (0.69 to 1.04) comparing the highest to lowest intake tertiles.ConclusionHigher intakes of LA and ALA were inversely associated with CVD and all-cause deaths in patients with diabetes. Proper dietary intakes of LA and ALA could contribute to the cardiovascular health and the long-term survival of patients with diabetes.